THE SINFUL TALK OF SIN - Tirimanna, Vimal (Asian Horizons, 2010)
Without the concept of sin, the sacrament of reconciliation has no meaning. If there is no sin, then, there is no need to reconcile! Monica Hellwig expresses this intrinsic link between the concepts of sin and reconciliation within the Christian tradition when she says that the sacrament of reconciliation “can be meaningful only if there is an authentic understanding of the pervasive need to ‘turn’ from one’s sins. In other words, the meaning of the sacrament of penance is dependent upon an understanding of the meaning of sin.” This article was originally published in Polish language in Homo Dei 297.4 (Sept-Oct 2010) 24-36.